Holographic entanglement entropy of a de Sitter braneworld with Lovelock terms. (25th January 2021) - Kushihara, Kouki; Izumi, Keisuke; Shiromizu, Tetsuya
Abstract: We examine the de Sitter entropy in the braneworld model with the Gauss–Bonnet/Lovelock terms. We find that the de Sitter entropy computed through the Euclidean action exactly coincides with the holographic entanglement entropy.